A renal abscess in the isthmus of horseshoe kidney - Balawender, Krzysztof; Orkisz, Stanisław; Biela, Przemysław; Sęk-Mastej, Anna (European Journal of Clinical and Experimental Medicine, 2017)
Horseshoe kidney (HSK) is the renal fusion anomaly caused by disturbances in embryonic development when the kidneys are fused together in the lower or upper pole forming an isthmus. The most common disorders in urinary tract related to horseshoe kidney are ureteral pelvic junction obstruction, urinary tract infection and urolithiasis. In our study, we present a rare case of an abscess in the isthmus of horseshoe kidney after extracorporeal shockwave lithotripsy on the right kidney was performed. The patient has had recurrent urolithiasis and underwent 4 treatments on the left kidney in the past without complications.